2019
DOI: 10.18510/hssr.2019.76112
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Future Music Teachers for Creative Self-Actualization

Abstract: Purpose of the study: The article deals with the problem of the readiness of future general education music teachers for creative self-actualization. The issue is regarded as an integral personality formation ensuring the achievement of creative self-actualization and including two interrelated components – professional readiness and personal readiness. Methodology: The research was carried out at the Institute of Philology and Intercultural Communication, Kazan Federal University, and based on the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Finally, higher education music teachers showed their motivation on enhancing music skills, mastering new music skills, and lifelong learning to realize the self-actualization need for the music professionalism. It was indicated that music teachers' professional readiness was combined by professional activities of musical, educational, and research (Yavgildina et al, 2019). The study agreed with that and confirmed that higher education music teachers showed the pursuit on the music professional readiness as the way to realize the fulfilled.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, higher education music teachers showed their motivation on enhancing music skills, mastering new music skills, and lifelong learning to realize the self-actualization need for the music professionalism. It was indicated that music teachers' professional readiness was combined by professional activities of musical, educational, and research (Yavgildina et al, 2019). The study agreed with that and confirmed that higher education music teachers showed the pursuit on the music professional readiness as the way to realize the fulfilled.…”
Section: Discussionsupporting
confidence: 68%
“…2019., p. 3]. *Address correspondence to this author at the Kazan Federal University, Institute of Philology and Intercultural Communication, Russia; Tel: +79178668372; E-mail: anastasia-vm2012@yandex.ru In such a situation, a person will need new competencies, a high level of creativity, which will be expressed in solving problems of organizing the work of the information society's elements (Akbarova, Dyganova, & Yavgildina, 2016, Maiorova, 2019., Salpykova, Akhmadullina, & Valiakhmetova, 2018)., Batyrshina, Kamalova, Dyganova, Murtazina, 2019). Consequently, a different approach to the formation, upbringing and education of these personality qualities is required.…”
Section: Introductionmentioning
confidence: 99%